2013
DOI: 10.1017/jtp.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Screening and assessment instruments for use in Indigenous-specific alcohol and drug treatment rehabilitation

Abstract: Objective: The study's aim was to review instruments suitable for assessing Australian Indigenous clients' treatment needs, and changes in wellbeing while receiving treatment for substance misuse at a culturally competent residential setting in north Queensland, Australia. Method: Searches of electronic databases, previously published reviews and websites was conducted. Instruments were selected according to their use in alcohol and drug treatment, developed for and/or validated with Australian Indigenous popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Existing studies show that it is possible to develop reliable and valid measures that are culturally appropriate and acceptable to Indigenous Australians [ 78 – 83 ], but the lack of measurement studies specifically related to community projects identified in this review (one study, see Fig. 1 ) clearly indicates that more of this measurement research is urgently needed [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies show that it is possible to develop reliable and valid measures that are culturally appropriate and acceptable to Indigenous Australians [ 78 – 83 ], but the lack of measurement studies specifically related to community projects identified in this review (one study, see Fig. 1 ) clearly indicates that more of this measurement research is urgently needed [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to validate psychometric measures before use in a cross-cultural Indigenous context ( Drew et al, 2010 ). Instruments to assess mental health and substance use ( Stephens et al, 2013 ), have been recently validated for Aboriginal Australians, but not tobacco smoking. This study uses the findings from a cross-sectional study of Aboriginal Australians to validate risk assessment scales for tobacco smoking in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with tool development within the wider population, briefness remains highly valued in the development of Aboriginal specific screening tools [33,34,51]. The screening tools have also generally maintained a closed system approach to screening [29,30,[52][53][54][55]. The effectiveness and appropriateness of closed system approaches to assessing risk is questionable for populations with complex and/or diverse needs as these groups have typically been excluded from the population based studies in which the risk criteria was determined from and validated with [50].…”
Section: Discussionmentioning
confidence: 99%